Largely varying patterns and trends of primary cancer-directed resection for gastric carcinoma with synchronous distant metastasis in Europe and the US: a population-based study calling for further standardization of care - Huang, Lei; Jansen, Lina; Verhoeven, Rob H. A.; Ruurda, Jelle P.; Van Eycken, Liesbet; De Schutter, Harlinde; Johansson, Jan; Lindblad, Mats; Johannesen, Tom B.; Zadnik, Vesna; Zagar, Tina; Magi, Margit; et al. (Therapeutic advances in medical oncology, 2021)
Aims: The role of resection remains debated in cases of metastatic gastric carcinoma (mGC). Some mGCs are technically resectable. At the population level, the real-world application of resection for mGC remains largely unclear in most Western countries. This large, population-based international investigation aimed to reveal the resection patterns and trends for mGC and the treatment-associated factors in Europe and the US. Methods: Data on cases with microscopically-confirmed primary invasive stomach carcinoma with distant metastasis were obtained from the nationwide cancer registries of the Netherlands, Belgium, Norway, Sweden, Estonia, and Slovenia and the US Surveillance, Epidemiology, and End Results-18 database. We calculated age-standardized rates of primary cancer-directed resection and assessed resection trends using linear regression. We investigated associations of treatment with patient and cancer factors using multivariable-adjusted log-binomial regression. Results: Among 133,321 patients with gastric cancer, overall, 40,215 cases with mGC diagnosed between 2003-2017 were investigated. Age-standardized resection rates significantly declined over time in the US, Belgium, Sweden, and Norway (by 5-14%). Resection rates greatly differed from 5% to 16% in 2013-2014. Cases with older ages, cardia tumors, or tumors involving adjacent structures were significantly less often operated across most countries. Sex was not significantly associated with resection. Across countries the association patterns and strengths differed largely. With multivariable adjustment, resection rates decreased significantly in all countries except Slovenia and Estonia (prevalence ratio per year = 0.90-0.98), and the decreasing trends were consistently observed in various stratifications by age and location. Conclusion: In Europe and the US, resection patterns and trends largely varied across countries for mGCs, which were mostly less often resected in the early 21st century. Various resection-associated factors were shown, with greatly varying association patterns and strengths. Our report could aid to identify discrepancies in clinical practice and highlight the great need for further clarifying the role of resection in mGCs to enhance standardization of care.
Gesehen am 21.01.2022